Engineering solar cells based on correlative X-ray microscopy. Issue 10 (9th May 2017) - Stuckelberger, Michael; West, Bradley; Nietzold, Tara; Lai, Barry; Maser, Jörg M.; Rose, Volker; Bertoni, Mariana I.
Abstract: Abstract : In situ and operando measurement techniques combined with nanoscale resolution have proven invaluable in multiple fields of study. We argue that evaluating device performance as well as material behavior by correlative X-ray microscopy with <100 nm resolution can radically change the approach for optimizing absorbers, interfaces and full devices in solar cell research. In this article, we thoroughly discuss the measurement technique of X-ray beam induced current and point out fundamental differences between measurements of wafer-based silicon and thin-film solar cells. Based on reports of the last years, we showcase the potential that X-ray microscopy measurements have in combination with in situ and operando approaches throughout the solar cell lifecycle: from the growth of individual layers to the performance under operating conditions and degradation mechanisms. Enabled by new developments in synchrotron beamlines, the combination of high spatial resolution with high brilliance and a safe working distance allows for the insertion of measurement equipment that can pave the way for a new class of experiments. Applied to photovoltaics research, we highlight today's opportunities and challenges in the field of nanoscale X-ray microscopy, and give an outlook on future developments.